2021
DOI: 10.1021/acs.energyfuels.1c03271
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrotreatment of Pine Sawdust Hydropyrolysis Vapor over Ni, Mo-Impregnated HZSM-5 for Optimal Production of Gasoline Components

Abstract: Noncatalytic hydropyrolysis of pine sawdust integrated with downstream catalytic vapor hydrotreating was conducted in a two-stage fixed bed reactor under 5 MPa H 2 . Among the catalysts used in the experiments (HZSM-5, 1%Mo-HZSM-5, 1%Ni-HZSM-5, and three NiMo-HZSM-5 catalysts of different metal loadings), bimetallic 1%Ni3%Mo-HZSM-5 acted as the best catalyst. The hydrotreatment with this catalyst at 320 °C converted the oxygenated bio-oil entirely into liquid hydrocarbons with a yield as high as 23.9% of dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[13][14][15] Hydropyrolysis of pine sawdust and subsequent hydrotreatment of the produced vapor over a reduced bimetallic NiMo over HZSM-5 showed the formation of 23.9 wt% of bio-oil with a high (∼72%) aliphatic hydrocarbon selectivity. 16 A similar strategy by Huang et al 17 over Mo-Cu/ HZSM-5 (500 °C, 1 h) showed an increased fraction of C 6 -C 12 hydrocarbons however with high residual solids. Cheng et al [18][19][20] investigated the liquefaction of pine sawdust using ethanol/water at supercritical conditions and employed zinc as an in situ H 2 generator for the upgradation of bio-oil over Pd/C and CoZn/HZSM-5.…”
Section: Introductionmentioning
confidence: 89%
“…[13][14][15] Hydropyrolysis of pine sawdust and subsequent hydrotreatment of the produced vapor over a reduced bimetallic NiMo over HZSM-5 showed the formation of 23.9 wt% of bio-oil with a high (∼72%) aliphatic hydrocarbon selectivity. 16 A similar strategy by Huang et al 17 over Mo-Cu/ HZSM-5 (500 °C, 1 h) showed an increased fraction of C 6 -C 12 hydrocarbons however with high residual solids. Cheng et al [18][19][20] investigated the liquefaction of pine sawdust using ethanol/water at supercritical conditions and employed zinc as an in situ H 2 generator for the upgradation of bio-oil over Pd/C and CoZn/HZSM-5.…”
Section: Introductionmentioning
confidence: 89%
“…6 The octane rating illustrates the antidetonation property of motor gasoline, which is more extensively used in the evaluation system of the motor gasoline quality after adjustment. 7 Fuel surrogates and derivate motor fuels can be used to decrease the influence of gasoline engines on the environment. 8 Various scenarios can be used to decrease the ecological influence of gasoline engine operation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, decreasing alkene concentrations of FCC gasoline became the concentration of synthesizing clean gasoline fuel . The octane rating illustrates the antidetonation property of motor gasoline, which is more extensively used in the evaluation system of the motor gasoline quality after adjustment …”
Section: Introductionmentioning
confidence: 99%